FROM THE EDITOR’S DESK - Dr. Fatema Jawad (Journal of the Pakistan Medical Association, 2025)
We bid farewell to the year 2025 and welcome and look forward to a more productive 2026.The submission of articles has increased in numbers amounting to a total of 2600 and we have published two Supplements in the past year. As the rules for authorship credit have changed by the regulatory bodies as HEC and PMDC, alarger number of articles are required for promotion. This leads to a convenient acquiring of authorship for the purpose. In fact unethical means are employed which needs enquiries and eventually removal of names. Authorshipfor sale, is a new method for acquiring the required number of publicatons. The first authors’ position can be as expensive as Rs.100,00.00. What are we heading for? A busyassistant physician working in a public hospital,and later doing private practice till midnight,has no time for dedicated research. Along with authorship misuse is also the extensive use of AI for research writing. No authors have the honesty to declare it. This is rather unethical and not expected from the educated sector ofthe society. I wish to express my gratitude to the colleagues who are responsible for the regularity of the publication of JPMA. Dr. Anwar Siddiqui has been contributing the most by performing most of the initial reviews. Dr. Mubeen, Dr. SinaAziz and Dr. Umair Sami make the core team, by checking the revised articles.The technical review is very professionally performed by Ms.Maria Najam, Ms. Rizwana and Mr. Humair. The major workload of the office of JPMA is shared by Mr.Adil, Mr. Faizan, Mr. Munib, Mr.Ghaffar. Mr. Hamza and Mr. Ramzan. Mr. Asif Bhojani has joined recently as the manager to replace Mr. Majid.Thanks and appreciation is for this JPMA team. It is my duty to thank all our learned peerreviewers and stats reviewers for their help and assistance. The Special Section, being published since the last ten years is a unique part of the journal. I extend my gratitude to the section editors, Dr. Sanjay Kalra from Karnal,India, writes for Primary Care Diabetes, Advancesin Endocrinology, Barocrinology and Advances inNephrology. Dr. Shahzad Shamim from Karachi,is the section editor for Neurooncology, Dr.Farooq Rathore from Quetta, is responsible for the Rehabilitation section and Dr. Aamna Hassanfrom Lahore takes care of the IMAGES Section. Ialso wish to acknowledge our readers as JPMAis widely read in all five continents. May the coming year 2026, bring wider readership for JPMA due to increasing numberof high quality research publications. We enter our 76th year of publication and we have grown. May God Bless all those who are affiliated with the journal.